2023
DOI: 10.1111/joop.12451
|View full text |Cite
|
Sign up to set email alerts
|

Understanding employee work‐life conflict experiences: Self‐leadership responses involving resource management for balancing work, family, and professional development

Abstract: The work–life conflict literature describes how employees manage conflict experiences, but little work has focused on experiences beyond work and family (or work and school) conflict to examine more broadly work, family, and professional development (e.g., when employees enter a graduate degree program). This study uses qualitative data to explore the work–life conflict experiences of employees undergoing professional career development in the form of gaining a graduate degree. We contribute to the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Indeed, a recent study on employees found that workers reported three types of work–life conflict experiences (energizing, depleting, and maintaining) and that each corresponded to different enacted self‐leadership strategies. For example, when employees report energizing experiences, they tend to utilize more behavioural strategies of self‐goal setting and self‐observation that facilitate them to acquire more coping resources (Williams & McCombs, 2023). As such, workers self‐leadership strategies play a crucial role in understanding and intervening to resolve work–life conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study on employees found that workers reported three types of work–life conflict experiences (energizing, depleting, and maintaining) and that each corresponded to different enacted self‐leadership strategies. For example, when employees report energizing experiences, they tend to utilize more behavioural strategies of self‐goal setting and self‐observation that facilitate them to acquire more coping resources (Williams & McCombs, 2023). As such, workers self‐leadership strategies play a crucial role in understanding and intervening to resolve work–life conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Catechists continue to bear witness to God's love and faithfulness even though the faithful are often in imperfection, error, and sin (Williams & McCombs, 2023). In preaching and teaching the catechists continue to realize that the life of faith is an ongoing process.…”
Section: Educatormentioning
confidence: 99%
“…Through a careful assessment of their personal perceptions and lived experiences, an in-depth inductive qualitative analysis was conducted to identify the mothers' special experiences in raising a child with intellectual disabilities. The author classified and analyzed transcripts using a step-by-step transcript analysis technique based on the IPA method [61,62], which included organizing, coding, integrating, and interpreting the data [63].…”
Section: Data Analysis and Validitymentioning
confidence: 99%